Pengaruh Brand Awareness, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Atap Plastik UPVC Maspion di Kota Bandung - Aenudin, Nisa Nuraeni; Saputro, Arie Hendra (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This research aims to analyze the influence of brand awareness, price and product quality on purchasing decisions for Maspion UPVC plastic roofs in Bandung City. This research uses quantitative methods with descriptive and verification approaches. Data was collected through questionnaires distributed to 100 respondents who were owners or managers of iron shops, building materials shops and material shops in the city of Bandung. The analysis technique used in this research is multiple linear regression with validity, reliability and classical assumption tests using SPSS 29. The results of the research show that partially, brand awareness, price and product quality have a positive and significant effect on purchasing decisions for Maspion UPVC plastic roofs. Simultaneously, these three variables also have a significant influence on purchasing decisions, with product quality as the most dominant factor. These findings indicate that increasing brand awareness, competitive pricing strategies, and improving product quality can be effective strategies for companies in increasing sales and competitiveness in the market.